The potential implementation of Agile Project Management in a manufacturing enterprise: The obstacles and solutions - Chen, Kuancheng (2019)
The changing business environment has brought the growing demand for effective project management approach. Agile project management approach, which has been given more increasing attention in recent years, puts emphasis on the continuing update to the business environment to provide correct outputs. It was observed that APM approach has been mainly introduced to the IT sector and software development project, and there was relatively less literature discussing applying APM in other industries or projects. This report is based on this research gap, and evaluate the applicability of APM in two different projects in a manufacturing company. This dissertation report conducted literature review on Traditional project management and Agile project management and applied semi-structured interviews with project managers at ABC Fitness- a fitness equipment manufacturer to collect primary data. The findings of this study identify the presence of agile elements and potential difficulties for applying APM at the company. Besides, this research developed a conceptual model revealing the relationships of different project stakeholders, and the effects that could affect the agility of project management.